DIGITAL AGE TOURISM: SOCIAL MEDIA'S ROLE IN HOSPITALITY AND INTERCULTURAL COMMUNICATION - Subekti, Priyo; Nugraha, Aat; Bakti, Iriana (Bajang Institute, 2025)
The growth of mobile devices and social media has greatly affected the tourism business, as well as hospitality and cross-cultural relations. This research studies the use of social media in transforming the tourism practices in Pangandaran focusing on ecotourism and river rafting in Citumang. Using the qualitative method, data were established by purposive sampling of three informants: tourism managers, tour guides and tourists. Through in-depth interviews, participatory observation, and social media posting and promotional materials documentation opened broad perspectives. The research results suggest that social media such as Instagram and Facebook are effective in marketing the Pangandaran’s ecotourism products. There are tour guides such as Kang Wahyu who use the site to tell a story in cultures and interact with tourists at the same time to enhance their experience and integration of cultures. However, limitations in these technologies’ full potential include poor internet coverage and low levels of digital skills among the local tourism providers. In conclusion, the results of the study indicate that combining social media with better digital infrastructure and participation of the community could improve the social and environmental aspects of ecological tourism.